Designing Biomaterial Platforms for Cardiac Tissue and Disease Modeling. Issue 1 (26th October 2020) - House, Andrew; Atalla, Iren; Lee, Eun Jung; Guvendiren, Murat
Abstract : Heart disease is one of the leading causes of death in the world. There is a growing demand for in vitro cardiac models that can recapitulate the complex physiology of the cardiac tissue. These cardiac models can provide a platform to better understand the underlying mechanisms of cardiac development and disease and aid in developing novel treatment alternatives and platforms toward personalized medicine. Herein, a summary of engineered cardiac platforms is presented. Basic design considerations for replicating the heart's microenvironment are discussed considering the anatomy of the heart. This is followed by a detailed summary of the currently available biomaterial platforms for modeling the heart tissue in vitro. These in vitro models include 2D surface modified structures, 3D molded structures, porous scaffolds, electrospun scaffolds, bioprinted structures, and heart‐on‐a‐chip devices. The challenges faced by current models and the future directions of in vitro cardiac models are also discussed. Engineered in vitro tissue models utilizing patients' own cells can potentially revolutionize the way we develop treatment and diagnostic alternatives. Abstract : Herein, current developments and applications of in vitro cardiac platforms for disease modeling are discussed. This article also discusses the types of cardiac models, their respective limitations, and prospects for developing better, more advanced cardiac tissue models to better mimic the native cardiac environment.